JPE Turnaround Times (Journal of Political Economy, 2022)
Previous articleNext article FreeJPE Turnaround TimesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreSummary Statistics of Turnaround Times, Current JPE Editors Outcome of 1st Round DecisionsDays to Decision MeanMedianDesk Rejection53%76Reject with Reviews41%9485Revise6%130118View Table Image Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 130, Number 10October 2022 Article DOIhttps://doi.org/10.1086/722479 Views: 494Total views on this site © 2022 The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.